(untitled) (Al-Farooq Journal of Sciences, 2026)
The international intervention in Libya in 2011 represented the first large-scale implementation of the Responsibility to Protect (R2P) principle under United Nations Security Council Resolution 1973, which authorized the adoption of all necessary measures to protect civilians during the Libyan uprising. This study aims to analyze the relationship between international intervention and the collapse of Libyan state institutions during the period 2011–2016 by drawing upon the literature on the Responsibility to Protect, humanitarian intervention, and state failure theories. The study adopts a descriptive-analytical approach through the examination of international documents, United Nations resolutions, and relevant academic literature. The findings reveal that the shift in the objectives of the intervention from civilian protection to supporting regime change, coupled with the absence of an effective post-conflict state-building strategy, contributed significantly to the dismantling of Libya’s security and military structures and the emergence of a substantial security vacuum. Furthermore, the proliferation of armed militias and the multiplication of centers of power deepened political fragmentation and weakened central authority. The study concludes that the Libyan case embodies the paradox of the Responsibility to Protect, whereby an intervention intended to safeguard civilians produced unintended consequences, including state fragility and prolonged instability.